A Review of Modern Slavery in Britain: Understanding the Unique Experience of British Victims and Why it Matters. Issue 1 (April 2022) - Heys, Alicia; Barlow, Craig; Murphy, Carole; McKee, Amy
This article offers an original contribution to the field of victimization studies by investigating the current context of, and responses to, British nationals who are victims of modern slavery in the UK (BVs). Through the examination of National Referral Mechanism and Duty to Notify statistics, a current picture of specific experiences of BVs in the UK is illustrated with reference to identification and access to support. An exploration of the reasons for non-engagement of BVs with services and the detrimental impact this may have on their recovery highlights pertinent issues of mistrust, stigma and shame. Compounded by the current criminal justice approach towards modern slavery, the effects on the well-being of victims and survivors document the barriers to accessing services. A lack of engagement with the complexity of modern slavery; a lack of knowledge, training and expertise; and a lack of comprehensive guidance result in poor outcomes for BVs. Overall, the findings of this article are important in recognizing that the needs of BVs are currently not adequately met. A comprehensive investigation is required to examine the specific needs and experiences of BVs so that responses can be improved to effectively and appropriately support them into long-term and meaningful recovery.